Upaya Menumbuhkan Kepedulian Lingkungan Siswa Di SDN 2 Bendogerit Melalui Pendampingan Guru Memanfaatkan Majalah Sains Digital Berbasis Kearifan Lokal Blitar - Surayanah; M. Anas Thohir; Ananda Zahra; Dhiya Nasywa; Dina Nur Abidah; Najin Fadila Foresta (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
This community service activity aimed to foster environmental awareness among students at SDN 2 Bendogerit by providing guidance to teachers on how to utilize a digital science magazine based on Blitar’s local wisdom. The method used was a quantitative descriptive approach with a pre-test and post-test design. The subjects of the activity consisted of teachers involved in guiding the use of digital learning media. Data were collected using a Likert-scale questionnaire and analyzed descriptively in the form of percentages. The results of the activity showed an improvement across all measured indicators. Students’ environmental awareness increased from 90% to 95%, the quality of teacher guidance improved from 82% to 94%, and teachers’ ability to utilize digital media increased from 77% to 92%. These findings indicate that teacher guidance in the use of digital science magazines based on Blitar’s local wisdom is effective in supporting contextual learning, enhancing teacher competencies, and strengthening environmentally conscious character among elementary school students.